Obeah, Orisa, and Religious Identity in Trinidad, Volume I, Obeah : Africans in the White Colonial Imagination, Volume 1 - Hucks, Tracey E., 1965- (Book collections on Project MUSE., 2022)
"Obeah, Orisa, and Religious Identity in Trinidad is an expansive two-volume examination of social imaginaries concerning Obeah and Yoruba-Orisa from colonialism to the present. Analyzing their entangled histories and systems of devotion, Tracey E. Hucks and Dianne M. Stewart articulate how these religions were criminalized during slavery and colonialism yet still demonstrated autonomous modes of expression and self-defense. In Volume I, Obeah, Hucks traces the history of African religious repression in colonial Trinidad through the late nineteenth century. Drawing on sources ranging from colonial records, laws, and legal transcripts to travel diaries, literary fiction, and written correspondence, she documents the persecution and violent penalization of African religious practices encoded under the legal classification of "Obeah." A cult of antiblack fixation emerged as white settlers defined themselves in opposition to Obeah, which they imagined as terrifying African witchcraft. These preoccupations revealed the fears that bound whites to one another. At the same time, persons accused of obeah sought legal vindication and marshaled their own spiritual and medicinal technologies to fortify the cultural heritages, religious identities, and life systems of African-diasporic communities in Trinidad."--